2019
DOI: 10.1051/bmdcn/2019090316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the serum β2 Microglobulin level in patients with systemic lupus erythematosus and its correlation with disease activity

Abstract: Background: Designation of disease activity is serious for the management of systemic lupus erythematosus (SLE). Serum level of β2 microglobulin (β2M) may be associated with illness activity in SLE disease. Since the role of β2M for assessing of illness activity in SLE is not completely clear, the current study aimed to discern evaluation of β2M in patients with SLE and its correlation with sickness activity. Materials and Methods: In this case-control study, 50 patients with SLE disease and 25 healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…In autoimmune disorders, the importance of monitoring of β-2M serum levels to assess disease activity has been highlighted lately. This study revealed that increased β2M levels were found in at least one third of SLE patients and correlated with the disease activity markers such as SLEDAI-2K, anti-dsDNA antibodies titer, and C4 component [48]. In addition, high serum level of β-2M is associated with musculoskeletal system involvement, hematological symptoms and vasculitis.…”
Section: World Journal Of Medical Oncologymentioning
confidence: 64%
See 1 more Smart Citation
“…In autoimmune disorders, the importance of monitoring of β-2M serum levels to assess disease activity has been highlighted lately. This study revealed that increased β2M levels were found in at least one third of SLE patients and correlated with the disease activity markers such as SLEDAI-2K, anti-dsDNA antibodies titer, and C4 component [48]. In addition, high serum level of β-2M is associated with musculoskeletal system involvement, hematological symptoms and vasculitis.…”
Section: World Journal Of Medical Oncologymentioning
confidence: 64%
“…The cause of elevated β-2M concentration in autoimmune disorders such as SLE patients is not fully understood. Some researchers suggest the β-2M increase may result from increased lymphocyte turnover in autoimmune disease, or the presence of immune complexes formed by β-2M with anti-β-2M antibodies removed by kidneys resulting in a lower percentage of kidney damage [48].…”
Section: World Journal Of Medical Oncologymentioning
confidence: 99%
“…In a study with 100 SLE patients, the serum β2M levels were found significantly higher in SLE patients when compared to the healthy control group (p < 0.001), and it was shown that there is a significant correlation between serum β2M levels and SLE activity indices such as anti-dsDNA, complement and hemoglobin levels and the Systemic Lupus Erythematosus Disease Activity index (SLE-DAI) [9]. In a study conducted by Aghdashi et al with 50 SLE pa-tients, the serum β2M levels were found to be significantly higher than healthy controls and were related to SLE disease activity (p < 0.001 and p < 0.001, respectively) [24]. In a similar study by Zychowska et al with 69 SLE patients, it was shown that serum β2M levels correlated with SLEDAI, complement 4 levels and anti-dsD-NA titers [25].…”
Section: Discussionmentioning
confidence: 96%
“…As most of the free β2M in the circulation is excreted by glomerular filtration, it may be used for measuring the GFR [23]. While the main source of serum free β2M is lymphocytes; an increase in the serum levels may be related either to renal dysfunction or to lymphocyte activation in lymphoproliferative or autoimmune diseases in patients with normal renal function [4,24]. In a study with 100 SLE patients, the serum β2M levels were found significantly higher in SLE patients when compared to the healthy control group (p < 0.001), and it was shown that there is a significant correlation between serum β2M levels and SLE activity indices such as anti-dsDNA, complement and hemoglobin levels and the Systemic Lupus Erythematosus Disease Activity index (SLE-DAI) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (2,7,17,18) have revealed that β2MG is linked to disease activity. On the contrary, Wakabayashi et al (19) demonstrated no significant association between serum β2MG level and SLE disease activity.…”
Section: Discussionmentioning
confidence: 99%